Productivity, health, and inequality in the intrahousehold distribution of food in low-income countries. - Pitt, Mark M.; Rosenzweig, Mark Richard; Hassan, Md. Nazmul (American Economic Review, 1990)
A model was developed that links nutrition, labor-market productivity, health heterogeneity, and the intrahousehold distribution of food and work activities in a subsistence economy. Many social scientists are interested in the disparity in nutrients received by women compared to men, particularly in South and West Asian societies. An empirical analysis was applied to individual and household-level data from Bangladesh, a country that exhibits large differences in calorie consumption and in the energy intensity of activity by age and gender. The results indicate that both the higher level and greater variance in the calories consumed by men relative to women partly reflect the greater participation by men in activities in which productivity is sensitive to health status.